Journalism in mobile collaborative applications - BURGOS, Taciana de Lima (2016)
This article was written intentioned to contribute to the debate on collaborative journalism in mobile applications. For this, the object of study is the collaborative application ComuniQ, available for mobile phones and tablets; it was released for free by “Sistema Jornal do Commercio de Comunicação” (System Journal of the Communication´s Commerce – Free Translation) in the State of Pernambuco. Our goal is to analyze the aforementioned app as a collaborative interaction support in order to understand collaborative phenomena in news through mobile platforms. As a study method, we used a hybrid approach to research that combined literature review and direct observation.DOI: 10.21204/2359-375X/ancora.v3n2p107-124